An Unusual Case of Hepatocellular Carcinoma in a Healthy Teenager - Onyinye Ugonabo MD; Yochita Pulipati MD; Adnan Elghezewi MD; Virginia Miller DO; Lawrence Logan CLS; Pantangi Pramod MD (SAGE Publishing, 2023)
Hepatocellular carcinoma (HCC) is a primary liver malignancy known to occur majorly in patients with liver cirrhosis or those with a harbinger of risk factors like viral hepatitis, autoimmune liver disease, alpha-1 antitrypsin deficiency, alcoholic liver disease, and nonalcoholic fatty liver disease. The incidence of HCC has risen in the past 2 decades and currently ranks as the sixth most common cause of cancer-related death worldwide. Most cases are seen in adulthood, and only a very small percentage have been reported in adolescents with risk factors. The 2 pathologic subtypes of pediatric HCC are classic and fibrolamellar. Here, we discussed a very interesting rare case of a healthy male teenager with no apparent liver disease or risk factor who presented with right-upper-quadrant pain, normal alpha-fetoprotein level, and abdominal ultrasound showing a large hepatic mass. A liver biopsy was positive for HCC with fluorescent in situ hybridization showing a PRKACA complex gene pattern, favoring the fibrolamellar type.